Can everyone tap into the housing piggy bank? Racial disparities in access to home equity - James N. Conklin; Kristopher Gerardi; Lauren Lambie-Hanson (Federal Reserve Bank of Atlanta, 2022)
An oft-touted benefit of homeownership is the ability to build and access equity, and in recent years the amount of "tappable" home equity held by US homeowners has reached historic levels. But more than one-quarter of recent applications for mortgage equity withdrawal (MEW) loan products were denied. Black and Hispanic homeowners' applications were denied at even higher rates: 44 percent and 32 percent, respectively. These racial disparities in denials are larger than those associated with purchase and rate/term refinance mortgage applications. Controlling for loan and borrower characteristics commonly used in the underwriting process significantly reduces the MEW disparities, with the Black-White denial rate gap falling by approximately 83 percent, and the Hispanic-White gap falling by 73 percent. In other words, seemingly race-neutral underwriting criteria in the MEW product space explain large differences in the extent to which minority homeowners can access their home equity.
Keywords: G21; G51; J15; 330; housing wealth; mortgage; home equity; racial disparities